Effect of Food Plant Species on Feeding Intensity of Native and Invasive Apple Snails (Ampullariidae) in Indonesian Paddy Ecosystems - Sato, Satoru; Trisnawati, Dina Wahyu (Department of Agrotechnology, Universitas Muhammadiyah Yogyakarta, 2026)
The golden apple snail, Pomacea canaliculata, is known to be an injurious introduced species in the rice ecosystem of Southeast Asia, while the native apple snails, represented by Pila scutata, have shown declining populations over various parts of the region. Dietary differences may contribute to the contrasts in ecological damages, but information regarding comparison studies involving agricultural and aquatic plants is limited. This report considers the feeding rates of P. scutata and P. canaliculata on rice, Oryza sativa, and two other aquatic plants, Ludwigia adscendens and Pistia stratiotes, using a standardized laboratory bioassay. In this investigation, the feeding rates of individual snails of P. scutata and P. canaliculata were determined on pre-weighed plant material after starving them for 24 hours. In the bioassay, the amount of plant material eaten by the snails and the ratio of the reduced or remaining weight to the initial weight were used to determine the feeding rates. In general, the amount of plant material consumed by P. canaliculata is much higher than that eaten by P. scutata over all the plant species (Mann-Whitney U test, Holm-corrected P < 0.05). In particular, the consumption of rice seedlings by P. scutata is characteristically low.